Réponses

  • Utilisateur Brainly
2013-04-18T19:27:37+02:00

1)a) (x-2)(2x+3)-(x-2)(x+4)

   =2x²-4x+3x-6-(x²-2x+4x-8)

   =x²-3x+2

 

b) (x-2)(2x+3)-(x-2)(x+4)

  =(x-2)(2x+3-x-4)

  =(x-2)(x-1)

 

2)a) f(0)=0²-3*0+2=2

f(3/2)=(3/2-2)*(3/2-1)=-1/2*1/2=-1/4

 

b) f(x)=0 donne (x-2)(x-1)=0

               donc x-2=0 ou x-1=0

               donc x=2 ou x=1

 

f(x)=2 donne x²-3x+2=2

           donc x²-3x=0

           donc x(x+3)=0

           donc x=0 ou x+3=0

           donc x=0 ou x=-3

 

3)a) (x-3/2)²-1/4=x²-3x+9/4-1/4

                            =x²-3x+8/4

                            =x²-3x+2

                            =f(x)

 

b) le minimum de f est -1/4 obtenu en x=3/2